2011
DOI: 10.1021/ja2002132
|View full text |Cite
|
Sign up to set email alerts
|

Facet Effect of Single-Crystalline Ag3PO4 Sub-microcrystals on Photocatalytic Properties

Abstract: We recently reported that Ag(3)PO(4) exhibits excellent photooxidative capabilities for O(2) evolution from water and organic dye decomposition under visible-light irradiation. However, very little is known about the shape and facet effects of Ag(3)PO(4) crystals on their photocatalytic properties. Herein we have developed a facile and general route for high-yield fabrication of single-crystalline Ag(3)PO(4) rhombic dodecahedrons with only {110} facets exposed and cubes bounded entirely by {100} facets. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
820
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,287 publications
(874 citation statements)
references
References 33 publications
18
820
1
10
Order By: Relevance
“…It can be seen that both the samples display broad absorptions in the UV and visible regions. As known, the Ag 3 PO 4 nanospecies could only show apparent absorptions in UV region, and in visible region with a wavelength shorter than 550 nm [16,17]. Accompanied by the abovementioned information deduced from the EDX elemental analysis and the XRD spectra shown in Figures 2 and 3, the present result further confirms the existence of metallic Ag species in our samples, which could arouse surface plasmon resonance absorptions in the visible region [9,10,41].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridsupporting
confidence: 87%
See 1 more Smart Citation
“…It can be seen that both the samples display broad absorptions in the UV and visible regions. As known, the Ag 3 PO 4 nanospecies could only show apparent absorptions in UV region, and in visible region with a wavelength shorter than 550 nm [16,17]. Accompanied by the abovementioned information deduced from the EDX elemental analysis and the XRD spectra shown in Figures 2 and 3, the present result further confirms the existence of metallic Ag species in our samples, which could arouse surface plasmon resonance absorptions in the visible region [9,10,41].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridsupporting
confidence: 87%
“…More recently, it has been reported that silver orthophosphate (Ag 3 PO 4 ) could be used as highly active visible-light photocatalyst for the photodegradation of organic pollutants [15]. To further enhance photocatalytic activity of this novel material, great efforts have been addressed in terms of morphology-control [16], size-control [17], and hybridization [18,19]. Nevertheless, besides these efforts, it is highly desirable to develop unique yet highly efficient Ag 3 PO 4 -based photocatalysts with enhanced photocatalytic activity to provide more varied and new opportunities for pollutant elimination, and to match the requirements of the future environmental issues.…”
mentioning
confidence: 99%
“…Their performance comparison revealed that {001}‐TiO 2 provided 1.79 and 3.22 times higher reaction rates than {010}‐ and {101}‐TiO 2 in photocatalytic degradation of methyl orange (MO), respectively (Figure 8d),60 as the {001} facet possessed higher surface energy and a larger number of coordinatively unsaturated Ti 4+ active sites. In another case, the Ag 3 PO 4 rhombic dodecahedrons enclosed by twelve {110} facets (Figure 8e) exhibited superior photocatalytic activity to the cubes bounded by six {100} facets (Figure 8f) in degradation of MO (Figure 8g) and rhodamine B (RhB) (Figure 8h) 61. The density functional theory (DFT) calculation revealed that the surface energy of {110} facets (1.31 J/m 2 ) was higher than that of {100} facets (1.12 J/m 2 ), indicating the higher reactivity of {110} facets.…”
Section: Facet Engineering For Mono‐component Photocatalytic Materialsmentioning
confidence: 99%
“…Ag 3 PO 4 with a bandgap of 2.4 eV has an exceptionally high photocatalytic efficiency due to the high separation of photoexcited electrons and holes [8][9][10]. In this work, the Ag 3 PO 4 photocatalyst was successfully prepared in weak acidity solution.…”
Section: Introductionmentioning
confidence: 99%